2011
DOI: 10.1103/physrevb.83.153304
|View full text |Cite
|
Sign up to set email alerts
|

Hopping conduction and magnetoresistance of a GaAs/AlxGa1xAs quantum well with embedded InAs dots

Abstract: Magnetoresistance and temperature-dependent conductance are measured in the sample made of a GaAs/Al x Ga 1−x As quantum well with self-assembled InAs dots. Conductance is analyzed by Mott's hopping theory; the localization lengths have been extracted at various gate voltages. The sample is in the transition from near to metal-insulator to the deeply hopping regime with the combined effect of the long-and short-range scattering potentials. The magnitude of the negative magnetoresistance increases with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When inserted into a twodimensional (2D) electron system the quantum dots form random repulsive scattering centres and reshape the scattering potential from ionized donors [1,2]. It has been reported that variable range hopping of electrons can take place when applying a large negative gate voltage [3], and Landau quantization and localization can coexist in this system [4].…”
mentioning
confidence: 99%
“…When inserted into a twodimensional (2D) electron system the quantum dots form random repulsive scattering centres and reshape the scattering potential from ionized donors [1,2]. It has been reported that variable range hopping of electrons can take place when applying a large negative gate voltage [3], and Landau quantization and localization can coexist in this system [4].…”
mentioning
confidence: 99%